Siglec‐9 is upregulated in rheumatoid arthritis and suppresses collagen‐induced arthritis through reciprocal regulation of Th17‐/Treg‐cell differentiation. (June 2017) - Wang, X.; Liu, D.; Ning, Y.; Liu, J.; Wang, X.; Tu, R.; Shen, H.; Chen, Q.; Xiong, Y.
Abstract: Sialic acid‐binding Ig‐like lectin‐9 (Siglec‐9) is a novel sialic acid‐binding member of the immunoglobulin superfamily and is broadly expressed on immune cells, which can inhibit both innate and adaptive immune responses through immunoreceptor tyrosine‐based inhibitory motifs. However, the exact role of Siglec‐9 in the pathogenesis of rheumatoid arthritis (RA) remains unknown. In this study, we determined soluble Siglec‐9 (sSiglec‐9) levels in the serum and synovial fluid of patients with RA and evaluated the relation between sSiglec‐9 levels and clinical factors. In addition, we investigated whether Siglec‐9 could alleviate collagen‐induced arthritis (CIA) development in mice and explored the molecular mechanisms involved. The results showed that, in the serum and synovial fluid of patients with RA, sSiglec‐9 levels were elevated. Thus, high sSiglec‐9 serum levels associated with disease severity in patients with RA. Furthermore, administration of recombinant human Siglec‐9 Fc chimera protein significantly attenuated collagen‐induced arthritis development in vivo and in vitro by reciprocal regulation of the differentiation of Th17 and Treg cells. Our findings collectively indicate that Siglec‐9 plays a potent immunosuppressive role in the pathogenesis of RA by reciprocal regulation of Th17‐/Treg‐cell differentiation. In conclusion, Siglec‐9 may serve as a potential diagnostic and therapeutic target for RA.